Pengaruh Pengetahuan Remaja di Yogyakarta setelah Diberikan Pendidikan Kesehatan Reproduksi - Mudita Sri Hidayah (J.Abdimas: Community Health, 2022)
Reproductive health education for adolescents is very important given the problems of adolescent reproductive health such as unwanted pregnancy, free sex, abortion, alcohol, and HIV AIDS. Youth reproductive health education activities as a step to support the BKKBN program in overcoming the TRIAD KRR problem. There are more than five cases of pregnancy in adolescents in Notoyudan Village. The method of implementing this service is education, FGD, pre and post tests and forming peer education groups for teenagers. The results of the activity showed that there was an increase in knowledge of the participants, namely before the counseling there were 2 participants from 30 teenagers (6.67%) with good knowledge, 8 people with sufficient knowledge (26.67%), and 20 participants with poor knowledge about reproductive health (66.66). %). After education about KRR, the percentage of participants who had good knowledge increased to 18 participants (60%), and 12 participants with sufficient knowledge (40%). It can be concluded that TRIAD KRR education needs to be implemented because it can increase knowledge about reproductive health in adolescents.